Peningkatan Pemahaman Hukum dan Produktifitas Wakaf di Pimpinan Ranting Muhammadiyah (PRM) Danurejo Kecamatan Mertoyudan Kabupaten Magelang - Dakum, Dakum; Machfiroh, Ade Safriani; Zahra, Fatimatuz; Nurmuhamad, Fendy; Pratama, Gito Aji; Sulistyo, Wahyu (Fakultas Hukum, Universitas Negeri Semarang, 2021)
Abstract This dedication was carried out after initial observation to partners, Muhammadiyah Branch Leader Danurejo Kec. Mertoyudan Regency. Magelang. Preliminary observations received information that, the state of partners is still limited in terms of understanding waqf law and increased productivity of waqf property. It is proven that, the registration of the waqf land certificate has not been carried out optimally, such as the process of certification of the land swap waqf that has not been completed for a long time. Waqf land is managed by 5 locations, only 2 locations have been certified and three locations have not been certified. In addition, endowments that are managed are still limited to the use of religious and educational facilities, not yet leading to productive activities. Under these circumstances, the dedication team is very much called to provide counseling and assistance to partners. The purpose of this service is so that partners can better understand waqf law, overcome issues related to waqf law, and can increase waqf productivity. The method used is counseling and assistance including; improvement of understanding of waqf law, process of waqf land certification, management of waqf land becomes more productive, and campaign of community movement likes to have waqf. Key words Waqf law; Productivity; Nadzir professionalism Abstrak Pengabdian ini dilaksanakan setelah observasi awal kepada mitra, Pimpinan Ranting Muhammadiyah (PRM) Danurejo Kec. Mertoyudan Kab. Magelang. Observasi awal mendapatkan informasi bahwa, keadaan mitra masih terbatas dalam hal pemahaman hukum wakaf dan peningkatan produktifitas harta wakaf. Terbukti bahwa, pendaftaran sertifikat tanah wakaf belum terlaksana maksimal, seperti proses sertifikasi tanah wakaf tukar guling yang sudah lama belum selesai. Tanah wakaf yang dikelola sejumlah 5 lokasi, baru 2 lokasi yang sudah tersertifikat dan tiga lokasi belum tersertifikat. Selain itu, wakaf yang dikelola masih sebatas digunakan sarana keagamana dan pendidikan saja, belum mengarah kepada kegiatan yang produktif. Berdasarkan keadaan tersebut, maka tim pengabdian sangat terpanggil untuk memberikan penyuluhan dan pendampingan kepada mitra. Tujuan pengabdian ini agar mitra dapat lebih memahami hukum wakaf, mengatasi persoalan terkait hukum wakaf, dan dapat meningkatkan produktifitas wakaf. Metode yang digunakan adalah penyuluhan dan pendampingan meliputi; peningkatan pemahaman hukum wakaf, peroses sertifikasi tanah wakaf, pengelolaan tanah wakaf menjadi lebih produktif, dan kampanye gerakan masyarakat gemar berwakaf. Kat Kunci Hukum wakaf; Produtifitas; Profesionalitas nadzir